Peningkatan Kualitas Pendampingan Anak Kanker melalui Integrasi Bimbingan Al-Qur’an bagi Orang Tua, Pembelajaran Adaptif Anak, dan Pelatihan Aplikasi Zahir bagi Staf Keuangan - Satria Kharimul Qolbi; Muhammad Syaiful Nurasman; Muhamad Arif Nugraha; Annas Rahmat Ramadhani; Dinda Amanda Ainun Nuzul; Mutia Taqina Gamat; Putry H. Nadeak (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
Children with cancer face multidimensional challenges encompassing psychological, spiritual, educational, and institutional aspects, requiring an integrated family-centered support approach. This community service program aimed to improve the quality of assistance for children with cancer through the integration of Qur’anic reading guidance and spiritual mentoring for parents, adaptive learning for children, and financial management training using the Zahir application for institutional staff. The program was implemented at the Indonesian Cancer Child Foundation (YKAKI) Bandung Branch from March to September 2025 using a participatory approach. Indicators of success included increased parental engagement in spiritual sessions, sustained learning participation among children, and improved staff competence in digital financial recording and reporting. The results showed that parents experienced emotional catharsis and enhanced spiritual resilience, children maintained learning motivation and continuity through flexible and humanistic instruction, and staff were able to conduct more orderly and accountable transaction recording and basic financial reporting. Overall, this collaborative and integrative model proved effective in addressing the complex needs of children with cancer and their families and demonstrates strong potential for replication in similar institutions with contextual adjustments.